Development of a PC-based network analyzer that presents the frequency response characteristics of a voice-grade data communication line - Lim, Roseller Benin (Animo Repository, 1996)
Existing implementation of network analyzers for determining frequency response of leased data communication lines involve the transmission of sinusoidal signals at different frequencies within the voice spectrum. This paper presents an alternative implementation procedure using the theories of Fourier and Digital Signal Processing. Furthermore, the Personal Computer (PC) was used to eralise lower cost and better flexibility.